Ventricular-arterial coupling parameters and its prognostic value in patients with decompensated heart failure - Z. D. Kobalava; O. I. Lukina; I. Meray; S. V. Villevalde (Российский кардиологический журнал)
Aim. To assess ventricular-arterial coupling (VAC) parameters and their prognostic value in patients with decompensated heart failure (HF).Material and methods. VAC parameters were evaluated upon admission using two-dimensional echocardiography in 355 patients hospitalized with decompensated HF. VAC was expressed as the ratio between arterial elastance (Ea) and end-systolic LV elastance (Ees). The optimal VAC range was considered 0,6-1,2. Parameters of left ventricular (LV) efficacy were calculated using the appropriate formulas. Differences were considered significant at p<0,05.Results. The median values of Ea, Ees and VAC were 2,2 (1,7;2,9) mmHg/ml, 1,8 (1,0;3,0) mmHg/ml and 1,32 (0,75;2,21) respectively. In 63% of patients, VAC disorders were detected: 55% of patients had VAC >1,2 (predominantly patients with HF with reduced ejection fraction (HFrEF)-79%), 8% of patients had VAC <0,6 (all patients with HF with preserved ejection fraction (HFpEF)). Normal VAC was observed in 78%, 42%, and 1% of patients with HFpEF, HF with mid-range EF and HFrEF, respectively. There was significant correlation between Ea/Ees ratio and levels of NTproBNP (R=0,35), hematocrit (R=-0,29), hemoglobin (R=-0,26), pulmonary artery systolic pressure (PAPs) (R=0,18), dimensions of left atrium (R=0,32) and right ventricle (RV) (R=0,32). After 6 months, rehospitalization with decompensated HF was recorded in 72 (20,3%) patients, 42 (11,8%) patients died. Ea decrease <2,2 mmHg/ml and PAPs increase >45 mmHg increased the risk of rehospitalization with decompensated HF and all-cause mortality 2,5 and 3,7 times, respectively.Conclusion. Impaired VAC was diagnosed in 63% of patients with decompensated HF. However, the increased risk of all-cause mortality and rehospitalization with decompensated HF over the 6 months was associated with Ea decrease <2,2 mmHg/ml and PAPs increase >45 mmHg.